A framework of pre-service teachers' conceptions about digital literacy: Comparing the United States and Sweden. (April 2020) - List, Alexandra; Brante, Eva W.; Klee, Holly L.
Abstract: We examine the conceptions of digital literacy of pre-service teachers in the United States (n = 188) and Sweden (n = 121). Pre-service teachers were asked to define digital literacy in an open-ended fashion and to select those skills that they considered to be essential for digital literacy from a list of 24 skills provided. Based on pre-service teachers' open-ended responses, four profiles of digital literacy conceptions, progressing in sophistication, were identified (i.e., technology focused, digital reading focused, goal directed, reflecting critical use). Moreover, pre-service teachers' selections of skills or competencies essential for digital literacy were used in cluster analysis. Profiles of digital literacy conceptions were consistent across open-ended and selected-response forms of assessment. Important similarities and differences in conceptions of digital literacy across the United States and Sweden are discussed, as are implications for improving teacher education. Highlights: Pre-service teachers' open-ended responses were analyzed and four conceptions of digital literacy were identified. Conceptions were technology focused, digital reading-related, goal directed, and critical use-based views of digital literacy. Conceptions of digital literacy were validated through cluster analysis. We compare the digital literacy conceptions of pre-service teachers in the United States and Sweden. Implications for instruction and pre-service teacher development are discussed.